LINC02678 as a Novel Prognostic Marker Promotes Aggressive Non-small-cell Lung Cancer - Jia, Dexin; Xing, Ying; Zhan, Yuning; Cao, Mengru; Tian, Fanglin; Fan, Weina; Huang, Jian; Cui, Yimeng; Gu, Ruixue; Cui, Yaowen; Liu, Yuechao; Zhang, Shuai; et al. (Frontiers in Cell and Developmental Biology, 2021)
Non-small-cell lung carcinoma (NSCLC) is considered to be a fatal disease and characterized by a poor prognosis. Long non-coding RNAs (lncRNAs) have been reported to act as biomarkers and therapeutic targets in solid tumors. However, the expression of lncRNAs and their clinical relevance in NSCLC remain undetermined. The gene expression data profiled in The Cancer Genome Atlas and Gene Expression Omnibus (GSE81089) were employed to screen differentially expressed lncRNAs in NSCLC. LINC02678 was found to be upregulated in NSCLC and exhibited hypomethylation of the promoter region in NSCLC tissues. LINC02678 (also called RP11-336A10.5) was associated with poorer overall survival and relapse-free survival in NSCLC patients. In vitro models of gain- and loss-of-function demonstrated that LINC02678 promotes NSCLC progression by promoting NSCLC cell proliferation and cell cycle progression, as well as inducing NSCLC cell migration, invasion and epithelial-mesenchymal transition. LINC02678 was primarily located in the nucleus and could bind with the enhancer of zeste homolog 2 (EZH2). Moreover, we found that LINC02678 knockdown impaired the occupancy capacity of EZH2 and trimethylation of lysine 27 on histone 3 (H3K27me3) at the promoter region of cyclin dependent kinase inhibitor 1B (CDKN1B) and E-cadherin, as confirmed by ChIP-qPCR. A mouse transplantation model further demonstrated that LINC02678 could promote the tumorigenic and metastatic capacities of NSCLC cells. We identified LINC02678 as a tumor promoter in NSCLC, which enhanced the growth and metastasis of NSCLC cells by binding with EZH2, indicating that LINC02678 may serve as a potential biomarker for cancer diagnosis and treatment.